The Problem of the Science-Faith Relationships in OBI - Obolevitch, Teresa (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
The main object of this paper is to present the investigations that have been made during recent years in OBI on the problems of the science-faith relationships. The methodology of this investigation is described, and some of the most important results mentioned.